La primera modernización teatral argentina y el surgimiento del teatro independiente - Ogás Puga, Grisby (Latin American Theatre Review, 2015)
The emergence of the Independent Theatre movement was a determining factor in promoting theatrical modernization in Argentina. This study shows how Independent Theatre spurred the negation of national models and exercised a form of patricide that was much more effective than previous attempts at aesthetic and ideological rupture. The most important impetus behind modernization was Roberto Arlt, whose extraordinarily innovative work established rich intertextual dialogue with European models.